A new dispersing method on silica fume and its influence on the performance of cement-based materials. (15th July 2016) - Lei, Dong-Yi; Guo, Li-Ping; Sun, Wei; Liu, Jiaping; Shu, Xin; Guo, Xin-Li
Highlights: The zeta potential of the modified silica fume is much higher than the commercial silica fume. The higher fluidity of S2 paste mainly benefits from improvement of dispersion of the modified silica fume. The modified silica fume increases the hydration rate and hydration degree of cementitious material. The micrographs show that the modified silica fume particles are homogeneously dispersed in S2. The mean value of Ca/Si atom ratio of the C-S-H gel in S2 with modified SF is lower than in S1 with commercial SF. Abstract: Because the agglomerated silica fume can't realize its filling effect, hydration nucleation effect and pozzolanic effect in cement-based composites, a new dispersing method on silica fume aiming to dispersing it fully is introduced. The influence of physical and chemical properties of the modified silica fume on performance of cement-based materials was investigated. In view of the presence of silanol groups and negative charges of silica fume surface, the zeta potential of silica fume surface becomes positive after reaction of silanol groups on silica fume surface and calcium ions in modification solution. The change of zeta potential generates stronger adsorption force to anionic polycarboxylate copolymer. This paper discusses in detail the effect of the modified solution with different concentrations and pH values on adsorption amount of calcium ions on the surface of silica fume, thereby the optimal modified system was determined. The optimized dispersion of the modified silica fume was characterized by infrared spectra and comparing with the result of the commercial silica fume. The performance of modified silica fume in the simulated cement pore solution was evaluated by zeta potential and adsorption amount of polycarboxylate copolymers on silica fume particles surface. Besides, laser particle distribution and SEM photos help us clarify the difference between the particle size distribution and microstructure of the modified silica fume and the commercial silica fume. Results show that zeta potential, adsorption amount of polycarboxylate copolymers on modified silica fume surface increases obviously, the homogeneous dispersion fraction of the modified silica fume in the simulated cement pore solution increases significantly. Furthermore, influence of modified silica fume on the performance of cement-based materials was evaluated. Results showed that the effects of modified silica fume on fluidity, mechanical properties, hydration heat, non-evaporable water, hydration products, pore structure and morphology of cement-based materials are optimizer than the commercial silica fume. And the Ca/Si ratio of the C-S-H gel of cement-based material containing modified silica fume is lower than that of cement-based material containing commercial silica fume.